ADAT PERNIKAHAN BATAK TOBA DAN MANDAILING: Perbedaan, Persamaan, dan Nilai-Nilai Sosial - Khotimah, Khotimah; Ghafur, Abdul; Usman, Usman; Kasmuri, Kasmuri; Siregar, Siti Nurholiza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article presents research on the marriage customs of the Batak Toba and Mandailing ethnic groups in Padang Bolak District, North Padang Lawas Regency. The Batak culture places a high value on the customs and traditions practiced in their daily lives. The purpose of this study is to understand the implementation of marriage customs for Batak Toba and Mandailing, two local cultural traditions of the region, and to identify the differences and similarities in marriage ceremonies between the two ethnic groups in Padang Bolak District. Additionally, the study aims to elucidate the values underlying these marriage customs. This research employs a qualitative approach with observation and in-depth interviews with purposively selected informants. The findings reveal that, despite differences in the procedures and rituals of marriage between the two groups, both remain deeply rooted in local cultural values and traditions. The implications of this research highlight the importance of recognizing and respecting cultural and religious diversity within society, as well as the need for a deeper understanding of local customs to strengthen inter-ethnic relations and promote inter-religious tolerance. A thorough understanding of marriage customs also contributes to the preservation and development of the rich cultural heritage in Padang Bolak District.